THE ROLE OF ART TECHNOLOGIES IN THE METHODICAL REGULATION OF THE VOCATIONAL EDUCATION PROCESS (Web of Teachers: Inderscience Research, 2023)
This article discusses the role of art technologies in the methodological systematization of the professional activities of future speech therapists.